Obesidad y nivel socioeconómico en escolares y adolescentes de la ciudad de Salta - Juiz, Celia I. (2002)
Fil: Juiz, Celia I. ANLIS Dr.C.G.Malbrán. Centro Nacional de Investigaciones Nutricionales Dr. Arturo Oñativia; Argentina.